Knowledge, views and experiences of gambling and gambling‐related harms in different ethnic and socio‐economic groups in New Zealand - Sue E. Walker; Max W. Abbott; Rebecca J. Gray (Elsevier, 2012)
Abstract Objective: To describe survey findings which measure broader gambling harms and provide benchmark data to evaluate an awareness and education program to minimise harm; part of NZ's public health approach to problem gambling. To assess whether previously reported ethnic and socio‐economic disparities are evident when researching broader gambling harms. Methods: An in‐home, nationwide survey captured data from a multi‐stage, random probability sample of 1,774 adults and 199 15-17‐year‐olds. Oversampling Māori (NZ's indigenous people), Pacific and Asian peoples, and people in areas of deprivation, allowed analysis by ethnicity and socio‐economic status. Results: Data show high participation levels; around 8 out of 10 people took part in at least one gambling activity in the previous 12 months. Type and frequency of activities was used to define four groups: infrequent gamblers (60.9%); frequent, non‐continuous gamblers (17.6%); frequent, continuous gamblers (4%); and non‐gamblers (17.5%). Self‐reported knowledge of the signs of gambling harm was high. Arguments about gambling and people going without/unpaid bills provided two indicators of broader gambling harm. Around one‐sixth of New Zealanders experienced each of these harms. Impacts were greatest for low‐income groups, Māori, and Pacific peoples. Conclusions: The proportion of New Zealander's experiencing broader gambling harms is much higher than the prevalence for problem gambling. Consistent with other research, results show the flow‐on impacts of problem gambling - on family, friends and communities. Implications: Measures can be developed to benchmark the wider harms of gambling and evaluate public health programs addressing harm at population and sub‐population levels.